Keanekaragaman Arthropoda Hama dan Musuh Alami Pada Pertanaman Kakao di Desa Sita Kecamatan Rana Mese Kabupaten Manggarai Timur - Maria Saskia Clarisa Hasiman; Titik Sri Harini; Rika Ludji (Fakultas Pertanian Universitas Majalengka, 2024)
This research aims to determine the types of Arthropod Pests and Natural Enemies on Cocoa Plantations (Theobroma cacao L.) in Sita Village, Rana Mese District, East Manggarai Regency. This research was conducted from July to August 2023. The method used in this research was direct observation in the field. The data collection techniques include direct collection techniques with the help of insect nets and using hands, pitfall traps and yellow sticky traps. Trapped arthropods will be collected, grouped and put into sample bottles then preserved for identification at the Plant Pest Science Laboratory, Faculty of Agriculture, Nusa Cendana University. The results of the research show that the types of arthropod pests found in cocoa planting areas (Theobroma cacao L.) have their respective roles, namely as pests and natural enemies. Arthropods that act as pests are: Conopomorpha cramerella, Helopeltis sp., Hyposidra talaca, Dasychira sp. and Toxopetra aurantii. Meanwhile, the arthropods that act as natural enemies are: Dolichoderus thoracicus, Pantala flavescens, Atrabrus erythrocephalus, Euborellia annulipes, Odontomacus monticola and Rainieria antennaepes. The most common population of pest arthropods found at the research location was Toxoptera aurantii with a total of 250 individuals. Meanwhile, the smallest number was Hyposidra talaca with a total of 27 individuals. Meanwhile, the most common population of natural enemy arthropods found at the research location was Dolichoderus thoracicus with a total of 284 individuals. Meanwhile, the smallest number was Rainieria antennaepes with a total of 29 individuals. The diversity index value of arthropod pests and natural fungi on cocoa plantations in Sita Village, Rana Mese District, East Manggarai Regency is 2.00567 which is included in category 1 < H' < 3, namely the medium category